TRI-LEVEL CASCADING CONTROL TO AUGMENT POWER QUALITY CONCERNS IN DISTRIBUTION NETWORKS - Tariq, Musfirah Binte; Siddique, Abubakar; Aslam, Waseem; Azam, Mehreen Kausar; Arfeen, Zeeshan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Power distribution systems have been affected by harmonic problems for decades. Harmonic currents can affect line voltage and direct to numerous adversative results including equipment overheating, failure of solid-state equipment, and restraint with communication systems. They deteriorate power quality by causing poor power factors and increasing total harmonic distortion. To reduce harmonics and to improve power quality, a grid-tie active power filter (APF) is introduced which eliminates both lower and upper-order harmonics. In this proposed paper, APF is used along with an LCL filter with versatile controlling techniques, Clarke’s and Park’s transformations are implemented in the paper. The proposed scheme can fulfill the problem faced in the power system due to non-linear loads. The results are simulated and validated using MATLAB/Simulink environment.